A Study on the Relationship between Functional Movement Screen Scores and Short Lane Freestyle Swimming Degrees in Student Swimmers - Ece Ervuz, Mehmet Yildirim, Hayrettin Gumusdag (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: This study aims to investigate the relationship between the Functional Movement Screen (FMS) scores of students taking swimming lessons and their 25-meter freestyle swimming degrees. Methods: A total of 12 male volunteering swimmers studying at Yozgat Bozok University Faculty of Sport Sciences were included in the study. The participants were aged 22.00±0.85, 79.05±11.63 kg in body weight and 178.91±5.03 cm in height. The FMS, a screening test to evaluate functional movement patterns, was applied to the students taking swimming lessons. The short lane freestyle degrees of those students were measured in a 25-meter swimming pool. Pearson Correlation analysis was used to examine the relationship between FMS scores and 25m swimming degrees, as the data showed a normal distribution. Results: When the relationship between the FMS scores of the students who took swimming lessons and the 25-meter freestyle swimming degrees was examined, a negative correlation and statistically significant relationship was found between the swimming degrees and the left hurdle step score (r=-0.656, p=0.021) and the FMS total score (r=-0.694, p=0.012). Conclusion: As a result, the FMS total scores of all the students who took swimming lessons participating in the study are above the critical limit of 14 points, and therefore it is safe to state that the participants have a low risk of injury. With the correct application of movement patterns with the help of FMS of the athletes, an increase in swimming performance can be achieved through developing swimming techniques. FMS can be a performance determinant.